Gminny Program Profilaktyki i Rozwiązywania Problemów Alkoholowych jako podstawowa forma realizacji zadań własnych gminy z zakresu profilaktyki i rozwiązywania problemów alkoholowych - Biniasz-Celka, Danuta (Studia Prawa Publicznego, 2020)
The system of preventing and resolving alcohol-related problems used in Poland gives municipalities (gminas), as territorial units, the fundamental role in it. The municipality council is obliged to establish a number of programmes on the basis of the act on municipality self-government, as well as the regulations of other acts, including the Act of 26th October 1982 on Upbringing in Sobriety and Counteracting Alcoholism (A.U.S.C.A.) of the Municipality Programme for Preventing and Resolving Alcohol-related Problems (LCPP&RAP). The programme takes into account the areas of action listed in Article 41 section 1 of the A.U.S.C.A. and the indications included in the recommendations developed by the National Agency for Resolving Alcohol-related Problems. It should be emphasized that the implementation of tasks in the field of preventing and resolving alcohol-related problems under the programme is part of the strategy for resolving social problems, and takes into account the operational objectives set out in the National Health Programme. The regulations of the A.U.S.C.A. also provide the municipality with a significant role in implementing actions to tackle alcohol addiction. The actions are taken on three levels by: (1) appointing a local community committee for resolving problems (Article 41 section 3), (2) determining within resolutions the maximum number of permits for the sale of alcoholic beverages and the rules of locating places of sale and serving alcoholic beverages (Article 12 sections 1–3), (3) issuing permits for the sale of alcohol (Article 18 section 1) and monitoring the legitimacy of using these permits (Article 18 section 8). In addition, the LCPP&RAP provides solutions regarding forms, methods and projects undertaken by the municipality. It is important to note that the municipality self-government, as a result of decentralization of the state, has received extensive competence to conduct its own policy on alcohol-related problems, which is why its role is crucial.